Sustainable Food Waste Practice Among Small Medium Enterprise (SME) Restaurant Operators in Peninsular Malaysia - Othman, Nur Azimah; Simpong, Derweanna Bah; Razak, Nurul, Fardila Abd; Saidi, Normaizatul Akma; Samengon, Harnidah; Ahmad, Ghazali (The journal of contemporary issues in business and government, 2021)
This study empirically investigates restaurant operators' role to implement sustainable food waste practices. Food waste is mostly associated with behaviours such as negligence or conscious decisions to throw out food. Restaurants have a credible share in municipal waste as one of the significant waste sources globally and in Malaysia. Therefore, this increases the necessity of study waste management practices among restaurants. This study is structured through a self-administered survey with the east coast restaurant operators directly involved in SME related businesses. With 250 respondents, the data were analysed using multivariate analysis using structural equation modelling (SEM) via PLS. An exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were executed to validate the scales. These findings can be deduced restaurant operators, through its dimensions, influence the adaptation mediating effects and create sustainable food waste practices.